2019
DOI: 10.1101/527242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical and thermodynamic properties of Aβ42, Aβ40 and α-synuclein fibrils: A coarse-grained method to complement experimental studies

Abstract: Mechanical and thermodynamic properties of Aβ 42 , Aβ 40 , and α-1 synuclein fibrils: A coarse-grained method to complement experimen-2 tal studies 3 Abstract 12 We perform molecular dynamics simulation on several relevant biological fibrils associated with 13 neurodegenerative diseases such as Aβ 40 , Aβ 42 , and α-synuclein systems to obtain a molecular un-14 derstanding and interpretation of nanomechanical characterization experiments. The computational 15 method is versatile and addresses a new subarea … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…CG-SMD simulations have proven to bridge the force-loading gap between in vitro SMFS data with in silico data obtained from aa-SMD simulations, distanced by orders of magnitude. 54 In addition, CG-SMD simulations require much less computational power, 59,60 enabling us to explore pulling speeds unfeasible to simulate via aa-SMD. 54 Here, we showed that Bbp:Fgα complex can withstand forces even higher than the previously investigated SdrG:Fgβ complex.…”
Section: Discussionmentioning
confidence: 99%
“…CG-SMD simulations have proven to bridge the force-loading gap between in vitro SMFS data with in silico data obtained from aa-SMD simulations, distanced by orders of magnitude. 54 In addition, CG-SMD simulations require much less computational power, 59,60 enabling us to explore pulling speeds unfeasible to simulate via aa-SMD. 54 Here, we showed that Bbp:Fgα complex can withstand forces even higher than the previously investigated SdrG:Fgβ complex.…”
Section: Discussionmentioning
confidence: 99%